2015
DOI: 10.1186/s13068-015-0403-z
|View full text |Cite
|
Sign up to set email alerts
|

Loss of function of folylpolyglutamate synthetase 1 reduces lignin content and improves cell wall digestibility in Arabidopsis

Abstract: BackgroundOne-carbon (C1) metabolism is important for synthesizing a range of biologically important compounds that are essential for life. In plants, the C1 pathway is crucial for the synthesis of a large number of secondary metabolites, including lignin. Tetrahydrofolate and its derivatives, collectively referred to as folates, are crucial co-factors for C1 metabolic pathway enzymes. Given the link between the C1 and phenylpropanoid pathways, we evaluated whether folylpolyglutamate synthetase (FPGS), an enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(48 citation statements)
references
References 90 publications
2
45
1
Order By: Relevance
“…Among them, secondary metabolism, photosynthesis, and the protein synthesis and degradation pathway were the top three, in which 16, 15, and 14 DAPs, respectively, were involved (Figure 4). A previous study reported that loss of function of folylpolyglutamate synthetase (FPGS) led to decreased lignin content and enhanced cell wall digestibility in Arabidopsis [23]. Thus, in our study, the high expression of FPGS in the alligator weed leaves could improve the lignin content in the cell wall in order to protect cells under LK stress.…”
Section: Go Term and Kegg Pathway Analyses Of Daps Under Lk Stressmentioning
confidence: 62%
“…Among them, secondary metabolism, photosynthesis, and the protein synthesis and degradation pathway were the top three, in which 16, 15, and 14 DAPs, respectively, were involved (Figure 4). A previous study reported that loss of function of folylpolyglutamate synthetase (FPGS) led to decreased lignin content and enhanced cell wall digestibility in Arabidopsis [23]. Thus, in our study, the high expression of FPGS in the alligator weed leaves could improve the lignin content in the cell wall in order to protect cells under LK stress.…”
Section: Go Term and Kegg Pathway Analyses Of Daps Under Lk Stressmentioning
confidence: 62%
“…Based on comparisons of in vivo and in vitro enzyme activities/kinetics during the switch from G to C-lignin accumulation, it appears that the major factor driving C-lignin appearance is the loss of monolignol methylation activity. Previous studies have suggested that the methylation status of lignin can also be affected through the activity of the C1 pathway enzymes that provide the methyl donor S-adenosyl-L-methionine (Srivastava et al, 2015). To determine whether there might be changes in C1 precursor supply coincident with the appearance of C-lignin biosynthesis, we examined the levels of transcripts of key C1 pathway enzymes (protein sequences given in Dataset S4) in the Cleome transcriptome database (Dataset S5).…”
Section: Additional Transcriptional Changes Potentially Associated Wimentioning
confidence: 99%
“…Field‐grown switchgrass transgenic lines with high sugar release or good growth phenotypes included those silencing or OE: (i) GAUT4, GAUT4 ‐knockdown (KD) lines down‐regulating expression of galacturonosyltransferase4 , a gene encoding an enzyme involved in pectin biosynthesis (Biswal et al ., Biswal, A.K., Atmodjo, M.A., Li, M., Yoo, C.G., Pu, Y., Lee, Y.‐C., Zhang, J.Y., Bray, A., King, Z., LaFayette, P., Mohanty, S.S., Ryno, D., Yee, K., Thompson, O.A., Rodriguez Jr, M., Winkeler, K., Collins, C., Yang, X., Tan, L., Sykes, R.W., Gjersing, E., Ziebell, A., Turner, G.B., Decker, S.R., Parrot, W., Udvardi, M.K., Mielenz, J., Davis, M.F., Nelson, R.S., Ragauskas, A.J., and Mohnen, D.); (ii) miRNA, miRNA156 ‐overexpression (OE) lines OE miRNA156, a regulator of plant developmental processes (Fu et al ., 2012); (iii) MYB4, MYB4 ‐OE lines OE PvMYB4, an R2R3‐type MYB repressor of the lignin biosynthetic pathway (Shen et al ., 2012, 2013); (iv) COMT, COMT ‐KD lines down‐regulating expression of caffeic acid O ‐methyltransferase, a lignin biosynthetic gene (Fu et al ., 2011); and (v) FPGS, FPGS ‐KD lines down‐regulating expression of folylpolyglutamate synthase 1 , a gene encoding a C1 metabolism enzyme believed to provide methyl groups for lignin biosynthesis (Srivastava et al ., 2015). …”
Section: Introductionmentioning
confidence: 99%